2007
DOI: 10.1097/brs.0b013e31805471fe
|View full text |Cite
|
Sign up to set email alerts
|

Erector Spinae Muscle Changes on Magnetic Resonance Imaging Following Lumbar Surgery Through a Posterior Approach

Abstract: Erector spinae muscle alterations mainly occur distal to posterior lumbar surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
58
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 31 publications
(51 reference statements)
6
58
0
4
Order By: Relevance
“…Experimental animal studies have found magnetic resonance imaging (MRI) changes due to denervation and myonecrosis of the posterior spinal musculature consequent to posterior surgery and retraction duration [10,11]. Human MRI studies have also detected posterior spinal muscle abnormalities [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental animal studies have found magnetic resonance imaging (MRI) changes due to denervation and myonecrosis of the posterior spinal musculature consequent to posterior surgery and retraction duration [10,11]. Human MRI studies have also detected posterior spinal muscle abnormalities [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Paradoxically, some operations designed to treat these various spinal disorders actually disrupt these muscles and, in turn, may lead to substantial functional deficits [12][13][14][15] or various pain syndromes [16][17][18] . Minimally invasive spine surgery techniques strive to minimize surgical trauma to these muscles, thereby preserving their function 19 .…”
mentioning
confidence: 99%
“…Using a computer-based image analysis system, we combined MRI data to measure the cross-sectional area of PVM. Gille et al 5 reported that fatty involution of the erector spinae muscles proximal to the decompression level was negligible, although it was more marked distal to the arthrodesis. The vascularization and innervation of these muscles are segmented with numerous vertical anastomoses.…”
Section: Discussionmentioning
confidence: 99%
“…From several anatomical and functional studies of PVM, 4,5,14,15,18 it is clear that muscle damage can result in postoperative PVM dysfunction. Intraoperative damage to the posterior supporting structures can lead to irreversible PVM atrophy.…”
Section: Discussionmentioning
confidence: 99%